Effects of the Church’s expiation and glorification rituals on the Spanish Civil War - Etxebarria, Itziar (2010)
The article analyses the psychosocial impact of the apologies about the role of the Catholic Church in the Spanish Civil war along two studies. The relational study showed that Blazquez’s apology was perceived with limited impact, being more important at a societal level than at a micro-social level, both, on direct or indirect victims. The experimental study showed that self-criticism reinforced guilt as well as the need for reparation, whereas glorification diminished them.